2018
DOI: 10.3390/f9060342
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tree Growth Rate on the Mechanical Properties of Douglas Fir Lumber in Belgium

Abstract: In the context of questioning the relevance of making Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) silviculture more dynamic in Wallonia, we evaluated the influence of growth rate on the potential of Douglas-fir lumber for structural uses. Therefore, six trees 120 to 180 cm in circumference at 1.5 m were felled in 11 stands whose age varied from 40 to 69 years (mean circumference of the trees ≈150 cm; initial planting density from ≈2200 to 4400 seedlings/ha). In total, 706 boards (38 × 100 mm 2 and 70 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…Timber from unthinned Norway spruce stands had better mechanical properties than timber from unthinned Sitka spruce stands, while an opposite trend could be found in thinned stands, in both specimen sizes. The presence of juvenile wood lowers all grade-determining properties, in line with previous studies on softwoods (Brüchert et al 2000;Henin et al 2018;Cameron et al 2015). Although the longitudinal position of the sample had effects on wood properties, the direction of the effects in this study was not as uniform as in previous studies (Brüchert et al 2000;Lindström et al 2009;Rais et al 2014;Simic et al 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Timber from unthinned Norway spruce stands had better mechanical properties than timber from unthinned Sitka spruce stands, while an opposite trend could be found in thinned stands, in both specimen sizes. The presence of juvenile wood lowers all grade-determining properties, in line with previous studies on softwoods (Brüchert et al 2000;Henin et al 2018;Cameron et al 2015). Although the longitudinal position of the sample had effects on wood properties, the direction of the effects in this study was not as uniform as in previous studies (Brüchert et al 2000;Lindström et al 2009;Rais et al 2014;Simic et al 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Compared with the findings of previous studies (Roblot et al 2008;Henin et al 2018;Simic et al 2018;Gardiner et al 2011;Larsson et al 1998;Wilhelmsson and Arlinger 2002) on the same species, all of the measured physical and mechanical properties were relatively high. All sample trees in this study from thinned stands represented final crop trees; therefore, the best material available at the end of the rotation of the stands due to the type of thinning implemented, which was thinning from below with systematic row thinning.…”
Section: Discussioncontrasting
confidence: 86%
“…While the mechanical and physical properties examined in the current study were shown by previous studies to vary with various different factors (such as specimen size, climate, silvicultural management…), the values of mechanical and physical properties reported in the current study were mostly in the range of previously reported values for the same species (Lavers, 2002;Grottal et al, 2005;Verkasalo and Leban, 2002;Moore et al, 2009;Gardiner et al, 2011;Larsson et al, 1998). The one exception were mechanical and physical properties of Douglas-fir boards, which were slightly higher than previously reported (Henin et al, 2018).…”
Section: Mechanical and Physical Properties By Specimen Sizesupporting
confidence: 51%
“…Empirical studies exhibited the potential of Douglas-fir's wood quality focusing on old (future-crop) trees (von Pechmann and Courtois 1970;Möhler and Beyersdorfer 1987;Sauter 1992). The simulated planting densities reflected the recommended current densities (Bayerische Staatsforsten 2012) and were comparable to planting densities from the literature for the Pacific Northwest from 300 to 2960 trees ha −1 (Scott et al 1998), for Switzerland from 1346 to 2790 trees ha −1 (Schütz et al 2015), for Belgium from 2200 to 4400 trees ha −1 (Henin et al 2018) and for Germany from 1000 to 4000 trees ha −1 (Weller and Spellmann 2014;Rais et al 2014) as well as from 500 to 4000 trees ha −1 (Klädtke et al 2012).…”
Section: Discussionmentioning
confidence: 58%